Application of MELCOR to Westinghouse 4-loop PWR severe accident and evaluation of RPV lower head performance - Le , Dai Dien; Bui , Thi Hoa; Vo , Thi Huong (Nuclear Science and Technology, 2014)
In this study, MELCOR computer code is used to simulate the progression of a severe accident initiated from station blackout (SBO) accident for a Westinghouse 4-loop PWR. The hydraulic system is modeled using control volumes and flow paths. The reactor pressure vessel and internals, the primary loops with a pressurizer, steam generators, containment and accumulators are simulated for steady state in a good agreement with reference data. The two scenarios concerning SBO are investigated. The first scenario simulates RCP seal leakage during SBO and the other is SBLOCA to highlight an effectiveness of accumulators as well as to compare with the first simulation. All active safety systems which depend on AC power are assumed to be unavailable in this analysis. The main result of the study is an evaluation of RPV lower head integrity during severe accidents. This is preliminary work and expected to give the experience for further studies in the severe accident in nuclear power plants.